1982
DOI: 10.1016/s0022-5347(17)52871-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Mapping of Nephroureterectomy Specimens Removed for Urothelial Cancer: Pathological Findings and Clinical Correlations

Abstract: The nature and extent of mucosal alterations in 30 consecutive surgical specimens removed for urothelial neoplasia were evaluated by systematic mapping. The findings correlated with pertinent pathological, cytological and clinical data. Generally, the grade of the principal neoplasm paralleled the degree of epithelial disturbance in the grossly normal urothelium, high grade carcinomas being associated consistently with severe changes and low grade cancers with hyperplasia only. Cytological studies reflected ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…2), which was confirmed by McCarron et al [10] based on mapping examinations of the NUE spec imens. In a review of the literature, however, Mazeman [3] found that only 4% of 380 patients with a ureteral tumor had more than one focus.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…2), which was confirmed by McCarron et al [10] based on mapping examinations of the NUE spec imens. In a review of the literature, however, Mazeman [3] found that only 4% of 380 patients with a ureteral tumor had more than one focus.…”
Section: Discussionsupporting
confidence: 53%
“…Seven of our 11 patients subsequent bladder carcinoma had previous NUE with bladder cuff removal, while in only 2 of the 11 patients ureteral partial resection with organ preservation was carried out. At any rate, the relevance of circumostial segments for subsequent bladder tumors does not seem to be as great as the propensity of urothelial carcinomas to grow multifocally [10], to recur -8-15% of the ureteral carcinomas were preceded by a bladder tumor [8,11] -or to become located prevesically. Kimball and Ferris [7] had pointed out the problem of the ureteral stump carcinoma after incomplete NUE already in 1934.…”
Section: Discussionmentioning
confidence: 98%
“…Histologic mapping studies of UUT-TCC have identified an association with urothelial changes ranging from dysplasia to carcinoma in situ in a substantial proportion of patients [8,9]. These changes, which often are not evident from gross inspection, are responsible for a high incidence (20-70%) of tumor recurrence in the ureteral stump or at the ipsilateral ureteral orifice in patients treated with conservative operations such as nephrectomy or incomplete ureterectomy [2,4,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Kimball and Ferris [1] in 1934 were the first to find a high tumor incidence in the ureteral stump remaining after simple nephrectomy performed for upper urinary tract transitional cell carcinoma. McCarron et al [2], who found microscopic and macroscopic multifocal disease in nephroureterectomy specimens removed for urothelial cancer, further established the need for total nephroureterectomy. Bloom et al [3] and Kakizoe et al [4] reported an incidence of 30-64% of tumor recurrence in the ureteral stump or around the ipsilateral ureteral orifice in patients treated with less than total excision of the upper tract.…”
Section: Introductionmentioning
confidence: 99%